Análisis semiótico de Jane Eyre de Charlotte Brontë - Zárate Castillo, Joselin Briggith (2023)
The present research work focuses on analyzing the English Literature novel Jane Eyre, by Charlotte Brontë; Greimas theoretical-methodological approach ´was used to establish the categories of significance of the novel through narrative programs, actantial roles, lexematic figures, the subject actant´s profile and the veridictory square from Greimaisan theory; the intention of this research is to enhance classic literature´s conservation and promotion at local and national level. The methodology used in this work was based on the qualitative approach, semiotic method; it is a basic, descriptive research of literary corpus, whose intentional sample corresponds to the literary work Jane Eyre. The technique used corresponds to the interpretation of data or content analysis and the instruments respond to Greimas semiotic theory. The general conclusions of this research are: the novel has 87 narrative sequences that have Jane Eyre as the main operating subject; all actantial roles (subject/ object, sender /receiver, helper/opponent) are associated with the symbol of female freedom questioned in English literature. In addition, it is also important to mention the evolution of the character as a liberal subject that is evident in the figurative route of the character who transits from prison to freedom; so, the work reveals the social changes of time around the female figure.